Counterintuitiveness and Ritual Efficacy in Early Modern Karelian Healing: An Application of the Ritual Competence Theory - Kohonen, Siria (Traditiones, 2018)
This article presents an application of Thomas E. Lawson and Robert N. McCauley’s ritual competence theory in order to study two early modern Karelian sages and their rituals, especially their healing rituals. I analyse how this application presents ritual efficacy in archived healing narratives, and how such an efficacy affects interpretations of the rituals and their performers. *** V članku je predstavljena uporaba teorije ritualne kompetence Thomasa E. Lawsona in Roberta N. McCauleya na primeru dveh zgodnjemodernih karelijskih modrecev in njunih obredov, posebej zdravilnih. Avtorica analizira, kako ta raba predstavlja ritualno učinkovitost v arhiviranih zdravilnih pripovedih in kako učinkovitost vpliva na interpretacijo obredov in njihovih izvajalcev. This article presents an application of Thomas E. Lawson and Robert N. McCauley’s ritual competence theory in order to study two early modern Karelian sages and their rituals, particularly their Healing rituals. I analyse how this application presents ritual efficacy in archived Healing narratives, and how such an efficacy affects Interpretations of the rituals and their Performers. *** The article illustrates the use of the theory of the ritual competence of Thomas E. Lawson and Robert N. McCauley in the case of two early-modern Carelian wises and their rituals, particularly medicinal. The author analyses how this use represents ritual efficacy in archived medicinal narratives and how effectiveness affects the interpretation of rites and their performers.